[Investment Criteria, Productivity and Economic Development]: Reply - Ranis, Gustav (Quarterly Journal of Economics, 1964)
Journal Article Investment Criteria, Productivity and Economic Development: Reply Get access Gustav Ranis Gustav Ranis Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 3, August 1964, Pages 496–498, https://doi.org/10.2307/1879482 Published: 01 August 1964